Sao Tome and Principe : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Sao Tome and Principe stands at the threshold of the oil era. The government's objective of stabilizing the non-oil primary fiscal deficit over the medium term is appropriate. Executive Directors support the government's approach to monetary policy, which is consistent with the flexible exchange regime and focuses on limiting inflation and enhancing credit access for entrepreneurs. Sao Tome and Principe's flexible exchange rate regime remains appropriate. Sao Tome and Principe's statistical framework suffers from serious weaknesses, and institutional capacity needs to be enhanced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet